Artificial Intelligence and Nursing: Looking Back at Florence Nightingale - Jeong, Suyong (근관절건강학회지, 2021)
Background: The reaction of nurses to the advent of artificial intelligence (AI) during the fourth industrial revolution eraremains questionable. Understanding Florence Nightingale’s achievements may provide valuable lessons that will behelpful to contemporary nurses. Aims: To understand Nightingale’s nursing philosophy and methods and providesuggestions for future nursing practice, education, research, and health policy. Source of evidence: Literature. Discussion/Conclusion: Just as Nightingale captured the situation of her time and introduced latest scientific methods,modern nurses need to learn from Nightingale’s drastic actions to meet social needs. Nursing can regain a solid humanisticfoundation by returning to core values of nursing and humanities, while simultaneously adopting state-of-the-arttechnologies. Implications for Nursing Policy: AI-driven technologies will advance nursing services and provide greaterhuman-centered and personalized care by eliminating iterative and labor-intensive tasks. Nursing educational policyshould support the advancement of nursing curricula to develop AI competencies and specialists within the nursing field KCI Citation Count: 0